DRAMATURGI DALAM MEDIA SOSIAL: ANALISIS PENGGUNAAN SECOND ACCOUNT INSTAGRAM SEBAGAI MEDIA PERSETERUAN ANTARA DUA GENG PADA REMAJA AMORAVIST DAN GLC - Aura Rifa Adzani (2023)
Instagram is now one of the most popular social media by all Indonesian people, especially teenagers. There are negative sides that arise from this, one of which is the emergence of the phenomenon of using second account Instagram. Second account that is used by users to express themselves freely. The free use of second accounts causes users to frequently abuse second accounts as media for conflict. The feud was felt by the Amoravist and GLC youth gangs. The purpose of this research is to find out the background of the use of second accounts in adolescents and what are the motives for the misuse of the use of second accounts as a media for conflict. This research is a qualitative research with a symbolic interaction model. Sources of data in this study were divided into two, namely primary sources by conducting interviews and direct observation of all informants and secondary sources obtained through literature and documentation. This study used six informants who were determined through a purposive sampling technique. The validity of the data in this study was carried out through the member check technique, by asking again the truth of the information that had been raised by all informants. The final results of this study indicate that there are several things behind the use of second accounts including, they need privacy space to be able to freely express their 'backstage' themselves, the influence of their friends who have previously been second account users, and the desire to uploading content that is not suitable for uploading on the first account. Then it was also found that the motive for the misuse of the use of second Instagram accounts as a media for feud by two gangs was the desire to show the solidarity of a friend.